Late-stage tumors induce anemia and immunosuppressive extramedullary erythroid progenitor cells. (October 2018) - Zhao, Lintao; He, Ran; Long, Haixia; Guo, Bo; Jia, Qingzhu; Qin, Diyuan; Liu, Si-Qi; Wang, Zhongyu; Xiang, Tong; Zhang, Jue; Tan, Yulong; Huang, Jiani; et al.
Abstract Impaired immunity in patients with late-stage cancer is not limited to antitumor responses, as demonstrated by poor vaccination protection and high susceptibility to infection1–3 . This has been largely attributed to chemotherapy-induced impairment of innate immunity, such as neutropenia2, whereas systemic effects of tumors on hematopoiesis and adoptive immunity remain incompletely understood. Here we observed anemia associated with severe deficiency of CD8+ T cell responses against pathogens in treatment-naive mice bearing large tumors. Specifically, we identify CD45+ erythroid progenitor cells (CD71+ TER119+ ; EPCs) as robust immunosuppressors. CD45+ EPCs, induced by tumor growth–associated extramedullary hematopoiesis, accumulate in the spleen to become a major population, outnumbering regulatory T cells (Treg s) and myeloid-derived suppressor cells (MDSCs). The CD45+ EPC transcriptome closely resembles that of MDSCs, and, like MDSCs, reactive oxygen species production is a major mechanism underlying CD45+ EPC–mediated immunosuppression. Similarly, an immunosuppressive CD45+ EPC population was detected in patients with cancer who have anemia. These findings identify a major population of immunosuppressive cells that likely contributes to the impaired T cell responses commonly observed in patients with advanced cancer. Large tumors induce anemia and expansion of CD45+ immature erythroid cells, which represent a major immunosuppressive population in the spleen, contributing to systemic suppression of T cell immunity in late-stage cancer.